2017
DOI: 10.22435/sel.v4i1.1446
|View full text |Cite
|
Sign up to set email alerts
|

Profil Penderita Tuberkulosis Paru Di Tiga Puskesmas Wilayah Kerja Kabupaten Pidie Propinsi Aceh

Abstract: Tuberkulosis adalah penyakit menular yang disebabkan oleh mycobacterium tuberculosis dan menjadi ancaman bagi kesehatan. Jumlah kematian oleh penyakit ini mencapai 2 juta jiwa setiap tahunnya di seluruh dunia. Indonesia termasuk satu dari lima negara dengan kasus tuberkulosis terbanyak terutama tuberkulosis paru. Salah satu propinsi di Indonesia dengan kasus tuberkulosis paru tertinggi adalah Aceh yaitu di Kabupaten Pidie. Penelitian ini bertujuan untuk mengetahui bagaimana profil penderita tuberkulosis paru d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…Similarly, a study also indicated that the distribution of tuberculosis cases in children aged 5-14 years was 62.5% (Nurwitasari & Wahyuni 2015). Another study conducted in Aceh also showed that the majority of pulmonary TB patients belonged to the productive age group (70%) (Hadifah et al 2017). This happened, because he had been infected with bacterium Mycobacterium Tuberculosis for a long time, but it did not immediately become a disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, a study also indicated that the distribution of tuberculosis cases in children aged 5-14 years was 62.5% (Nurwitasari & Wahyuni 2015). Another study conducted in Aceh also showed that the majority of pulmonary TB patients belonged to the productive age group (70%) (Hadifah et al 2017). This happened, because he had been infected with bacterium Mycobacterium Tuberculosis for a long time, but it did not immediately become a disease.…”
Section: Discussionmentioning
confidence: 98%
“…Family is the closest contact with pulmonary TB patients. If the number of family members is large enough, the risk of transmission to vulnerable groups (toddlers) will also increase (Hadifah et al 2017). The source of transmission of TB infection in children comes from the closest family members, which are parents or caregivers who live together for a long time (Nurwitasari & Wahyuni 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This study is in line with a survey conducted by Ridwan et al in Pontianak in January 2017 -September 2018, stating that the most gender is male as many as 51 patients (64.6%). Another study conducted by Hadifah et al in three health centers in the working area of Pidie Regency found that the most gender was male with 13 patients (65.0%) (Hadifah, Manik, Zulhaida, & Wilya, 2017).…”
Section: Gendermentioning
confidence: 94%
“…Penyakit ini lebih menular selama masa inkubasi dibandingkan pada saat mengidap penyakit yang akan menginfeksi 10-15 orang per tahun apabila tidak diobati. Tuberkulosis (TB) merupakan masalah kesehatan global sebagai penyebab utama kematian pada jutaan orang setiap tahun di seluruh dunia setelah human immunodeviciency virus (HIV) (Hadifah, Manik, Zulhaida, & Wilya, 2017;Kim, Makhene, Sizemore, & Hafner, 2012) WHO memperkirakan setidaknya ada 10,4 juta kasus TB baru (insiden) di seluruh dunia, di mana 5,9 juta (56%) di antaranya adalah pria, 3,5 juta (34%) di antara wanita dan 1,0 juta (10%) di antara anak-anak. Bahkan berdasarkan data dari WHO menyebutkan bahwa Indonesia termasuk dalam negara yang menyumbang 60% dari kasus baru setelah India, Cina, Nigeria, Pakistan, dan Afrika Selatan (WHO, 2016).…”
Section: Pendahuluanunclassified